BIOSYNTHESIZED SILVER NANOPARTICLES USING CATHARANTHUS ROSEUS AND THEIR ANTIBACTERIAL EFFICACY IN SYNERGY WITH ANTIBIOTICS; A FUTURE ADVANCEMENT IN NANOMEDICINE - GUPTA, MONIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This research work develops an approach to synthesize silver nanoparticles (AgNPs) by reduction of leaf extract of Catharanthus roseus plant. This study produces synthesized nanoparticles that have process-controlled attributes which make their antibiotic action highly efficient. These attributes include smaller size, proper morphology, uniform dispersion, metal ion content, and formation of functional groups. By optimizing the reduction process parameters, AgNPs gain the desired properties. Methods: The biosynthesis of AgNPs process was performed using reaction of 10% (w/v) C. roseus leaf extract with AgNO3. The optimum conditions and concentration used for synthesis of nanoparticles were: 1 mM AgNO3, pH 5, and temperature 80°C with an incubation time of 72 h. All the above parameters were analyzed by ultraviolet-visible spectrophotometer with the surface plasmon resonance peak obtained at 440 nm. Results: Various characterization techniques were performed, namely, scanning electron microscopy, energy-dispersive X-ray, transmission electron microscopy, photoluminescence study, X-ray diffraction spectroscopy, Fourier transform infrared, dynamic light scattering, and atomic force microscopy. The results obtained from characterization confirmed the spherical morphology of the nanoparticles with size between 50 and 87 nm. In the current investigation, the antimicrobial activity of biosynthesized AgNPs was also determined using minimum inhibitory concentration and zone of inhibition methods against six different bacteria at different doses of AgNPs (100, 150, and 200 μg/ml) alone and also in combination with antibiotic-streptomycin. Conclusion: The results revealed that high concentration of AgNPs inhibits the bacterial growth. Furthermore, AgNPs revealed much stronger antibacterial action in synergy with streptomycin against antibiotic-resistant bacteria.